Improving Reading Skills Using Media Compic (Computer Picture) in Elementary Schools - Fajrudin, Lili; Hartati, Tatat (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Research aims to provide additional resources for teachers in elementary schools in selecting Indonesia language learning media , and their learning Indonesian is still a pragmatic and functional , the existing problems in the field, found learning the Indonesian language less use of instructional media as learning resources, the learning process is very dependent on student and teacher textbooks only. The lack of use of media and assistive devices or teaching aids during learning and the absence of teacher efforts to develop Indonesian language material and do not pay attention to the needs of students, especially reading material, reading is a basic foundation for children because it supports the learning process for all material in elementary school. The use of media Compic (Computer picture ) in accordance with the concept of learning to learn from the easy to the more difficult , expected researchers to teachers Indonesia language become a reference media in the learning process, especially for the improvement of reading in elementary school. In this research the authors used the library method. Data analysis techniques used is content analysis, which be obtained results that by using the Media learning Compic (Computer Picture ) in learning the language Indonesia especially reading material, reading skills of students in elementary schools , especially in low grade can be improved